Comparative Evaluation of Upper Airway Dimensions and Oxygen Saturation in Completely Edentulous Patients with and Without Dentures (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: sleep disordered breathing; obstructive sleep apnea; epworth sleepiness scale